The novelty of musical composition and poem patterns in the poetry of Nazir al-Azma - يونس, حسن; يعقوب البيطار; زكوان العبدو (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Nazir Al-Azma realized that the traditional musical form of the Arabic poem is based on rhythmic capabilities based on the principle of refined cumulative symmetry. Al-Azma wrote many poems according to this system, which indicates his mastery of it. In the sense that the innovation intended here is a departure from the prosodic rules enacted by Al-Farahidi in a relative departure, and the ancients tried to present musical proposals for the poetic verse that go beyond the inherited constant, in proportion to the development of the social life of Arabs throughout the ages, and these attempts receive their echoes in the poetry of greatness, and this is what will stand His research, with the emphasis that most of the poems of traditional greatness depend on the well-known Khalili form, and accordingly; The research seeks to study the modernity of the musical formation and the patterns of the poem in the poetry of Nazir al-Azma, by studying three styles represented by (the vertical poem), (the verbal poem), and (the prose poem).